REHABILITATION POTENTIAL OF PRE-LINGUISTIC CHILDREN WITH COCHLEAR IMPLANT IN THE ASPECT OF COHERENT SPEECH MASTERING - Ольга Юрьевна Синевич (Мать и дитя в Кузбассе, 2018)
The article assesses the rehabilitation potential of pre-lingual children with a cochlear implant in the aspect of mastering their coherent speech. For this purpose, a study was conducted, which participants were three groups of subjects. These are early deaf children, implanted after 4 years; children with IV degree of sensorineural hearing loss; normally developed children. It was found that the late implantation of a pre-lingual child with his subsequent stay among peers and adults with hearing impairment does not provide intensive spontaneous speech development, despite the regular nature of correctional work. Pre-lingual children with a cochlear implant have higher rates of coherent speech development, their communication is carried out without the use of dactyl and sign language.